Exploring the Status of Geospatial Skills within Local Authorities in Zimbabwe - Karimazondo, Norman (International Journal of Scientific Research in Computer Science and Engineering, 2020)
Some evidence for geospatial skills shortage have been revealed by surveys that were done in developed countries such as New Zealand, Australia, the United Kingdom (UK) and the United States of America (USA). However, most of the reported skills shortage are not sector specific and there is lack of information regarding extent of the geospatial skills shortage and its dimensions. In this study, an online survey was done to explore the scope of the geospatial skills shortage within the local authorities in Zimbabwe. The results of the survey indicate that demand for geospatial skills is very high, but supply is critically low with local authorities facing severe shortages particularly in remote sensing skills. Some of the key drivers behind the current geospatial skills shortage are lack of suitably qualified and experienced graduates, higher education training, awareness regarding geospatial technologies and the related career opportunities. This study recommends the development of clear geospatial graduate pathways for recent graduates wishing to gain initial experience in the geospatial industry and supporting current geospatial staff to obtain skills and recognised geospatial qualifications.